2022
DOI: 10.3390/ijms23158530
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for the Treatment of Squamous Cell Carcinoma: Potential Benefits and Challenges

Abstract: Melanoma and nonmelanoma skin cancers (NMSCs) are recognized as among the most common neoplasms, mostly in white people, with an increasing incidence rate. Among the NMSCs, squamous cell carcinoma (SCC) is the most prevalent malignancy known to affect people with a fair complexion who are exposed to extreme ultraviolet radiation (UVR), have a hereditary predisposition, or are immunosuppressed. There are several extrinsic and intrinsic determinants that contribute to the pathophysiology of the SCC. The therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 140 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…However, for advanced or metastatic non-resectable cancers, management has transitioned to an immunotherapeutic approach [56]. The treatment of advanced BCC focuses on Shh inhibition, while therapy for SCC interferes with the PD-1/PD-L1 checkpoint [57,58].…”
Section: Therapeutic Considerations For Skin Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…However, for advanced or metastatic non-resectable cancers, management has transitioned to an immunotherapeutic approach [56]. The treatment of advanced BCC focuses on Shh inhibition, while therapy for SCC interferes with the PD-1/PD-L1 checkpoint [57,58].…”
Section: Therapeutic Considerations For Skin Cancermentioning
confidence: 99%
“…For patients with SCC, surgical excision is the treatment modality of choice; however, for patients with increased risks of local recurrence, perineural spread, and metastasis, immunotherapy with cemiplimab, pembrolizumab, or nivolumab have been considered [55,58]. These drugs are PD-1 inhibitors, which inhibit the PD-1/PD-L1 immune checkpoint that typically decreases T cell functionality in the TME, suppresses the immune system, and accelerates cancer cell proliferation [58,60]. Therefore, treatment with these immunotherapy agents increases the volume of cytotoxic CD8+ T cells in the TME, allowing for tumor cell destruction [58].…”
Section: Therapeutic Considerations For Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence has suggested that ESCC should be viewed as a specifc disease that is extremely diferent from EAC clinically and biologically [2,4]. Recent studies even found that with a high burden of tumor mutation, massive infltration of infammatory cells, and increased expression of immunosuppression, ESCC seems to be associated with a favorable tumor microenvironment that could have a good response to ICIs [43]. Terefore, it was necessary to investigate the efciency and toxicity of frst-line chemoimmunotherapy in ESCC which also aligned with the principles of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, anti-PD-1 and PDL-1 inhibitors are used as immunotherapy for cancers with very good results [ 105 ]. Monoclonal antibodies against PD-1 have been tested in clinical trials for SCC including cemiplimab for the treatment of advanced cutaneous SCC and pembrolizumab for recurrent/metastatic cutaneous SCC [ 106 ]. It has been observed that T cells, Langerhans cells, and the expression of PDL-1 gradually increase during the progression from AK to in situ and invasive SCC, justifying the potential efficacy of their treatment with anti-PD-1/PDL1 immunotherapy [ 107 ].…”
Section: Future Perspectives In Immunotherapy For Actinic Keratosesmentioning
confidence: 99%